The Faithful Skeptics: Evangelical Religious Beliefs and Perceptions of Climate Change - Carr, Wylie Allen (Journal for the study of religion, nature and culture, 2012)
Polling data has indicated that evangelical Christians tend toward skepticism about the existence of anthropogenic climate change. Recognizing that evangelical Christians compose a politically influential population, we conducted interviews with pastors and lay members of churches in Dallas, Texas to assess the relationship between their religious beliefs and their views on climate change. In-depth interviews showed more complex relationships between religious and climate beliefs than has been documented by previous survey-based research. The interviews revealed a set of interrelated religious beliefs, namely in biblical inerrancy, God’s sovereignty, human sinfulness, eschatology, and evangelism, from which evangelicals draw to describe their perceptions of climate change. Our analysis shows how common belief interpretations contribute to skepticism of human-induced climate change for many interviewees. We also describe how alternative interpretations of these same beliefs promoted environmental concern and even acceptance of anthropogenic climate change among other interviewees. Results suggest the need to account for how faith shapes the complex and nuanced environmental beliefs that evangelicals hold.